Dwight Macdonald, language, and the discourse of the downward spiral - Lewandowski, Tadeusz (Stylistyka, 2020)
Dwight Macdonald’s writings on English designated the source of the language’s corruption in one ofits homelands: the United States. In “Updating the Bible” (1953), “The Decline and Fall of English” (1962), and his analysis of the third edition of Webster's New International Dictionary “The String Untuned” (1962), Macdonald presented a discourse that amounted to a call for the maintenance of standards in the face of a cultural and academic climate permeated by permissiveness, which to his mind debased English by rendering it less precise, aesthetically beautiful, and effective in communication. Countering this perceived downward spiral, therefore, became his main concern.